Optimization Of Parameters Of A Rod Intensifier Of A Potato Digger With The Method Of Mathematical Planning - Juraev Bakhodir Botirovich; Azizov Shavkat Abdurakhmanovich (Zien Journals, 2024)
In this article, the method of mathematical planning of multifactorial experiments is used to determine the optimal values of the parameters of a potato digger equipped with an elastic rod intensifier, obtained in single-factorial experiments. It is assumed that the influence of factors on the evaluation criteria is fully explained by a second-order polynomial, and the experiments were carried out according to the Hartley-4 (X4) plan
Keywords: optimization; parameter; intensifier; potato